1996
DOI: 10.1046/j.1365-2443.1996.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of DNA non‐homology lowers the initiation of meiotic recomination in yeast

Abstract: Background: Meiotic recombination between homologous chromosomes in the yeast Saccharo-myces cerevisiae is initiated by the formation of DNA double-strand breaks (DSBs). The mechanism of DSB formation and the factors that determine their frequency and location have yet to be elucidated. Current studies of meiotic recombination are also concerned with the question of the functional relationship between DSB formation and the other meiotic processes of homology searching, pairing and synapsis of homologues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…For a meiotic DSB to function efficiently as a recombination initiator, i.e., for a heteroduplex to form, the allelic sequence must be present in the homolog. Thus, promoter deletions, even if heterozygous, should interfere with the initiation of recombination, as they do in yeast, where they lower both DSB formation and the frequency of conversion of a downstream marker (33). We found that the bz-s39.8 deletion, which includes the bz promoter, caused a major reduction in the conversion frequency of heteroalleles on the 5′, but not the 3′, half of the gene (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…For a meiotic DSB to function efficiently as a recombination initiator, i.e., for a heteroduplex to form, the allelic sequence must be present in the homolog. Thus, promoter deletions, even if heterozygous, should interfere with the initiation of recombination, as they do in yeast, where they lower both DSB formation and the frequency of conversion of a downstream marker (33). We found that the bz-s39.8 deletion, which includes the bz promoter, caused a major reduction in the conversion frequency of heteroalleles on the 5′, but not the 3′, half of the gene (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Additional evidence for interactions between homologs that are independent of recombination comes from studies of DSB induction in diploids that are either homozygous or heterozygous at the DSB site. Heterozygosity decreases the frequency of DSBs, suggesting that homolog recognition precedes and promotes the initiation of recombination Rocco and Nicolas 1996).…”
Section: Is Recombination Required For Pairing?mentioning
confidence: 99%
“…FISH studies of homolog pairing indicate that at least some homolog recognition occurs in the absence of DSBs (Loidl et al 1994;Weiner and Kleckner 1994;Nag et al 1995;Rockmill et al 1995). In studies of DSB induction, the level of breakage on one chromosome was found to be affected by sequences present on the homolog, suggesting that homologous chromosomes normally associate with each other prior to the formation of DSBs (Xu and Kleckner 1995;Bullard et al 1996;Rocco and Nicolas 1996). Timecourse analyses indicate that DSBs are formed early in meiotic prophase prior to the initiation of SC formation (Padmore et al 1991).…”
Section: How Do Telomeres Promote Pairing?mentioning
confidence: 99%